Application of intravoxel incoherent motion imaging in the study of migration and movement of cancer cells - Wang, Yilei; Xu, Haixiao; Ahmed, Idris Jerjes (Cellular and Molecular Biology, 2020)
IVIM imaging technology can obtain physiological information of tissue cells and blood perfusion at the same time in one imaging process. Taking female patients in Shenzhen Maternal and Child Health Hospital affiliated to Southern Medical University as an example, the migration and movement of breast cancer cells and hepatocellular carcinoma cells are studied by intravoxel incoherent motion imaging. Apparent diffusion coefficient (ADC), true diffusion coefficient (D), pseudo-diffusion coefficient (D*) and perfusion fraction (f) are measured by the IVIM bi-index model, and statistical analysis is made. The results show that the IVIM bi-index model can truly reflect the diffusion of water molecules in breast mass-like lesions, and reflect the migration and movement of breast cancer cells. Especially D value has important reference significance for the research and diagnosis of breast cancer cells. IVIM bi-index model has limited diagnostic value for the migration and movement of common hepatocellular carcinoma cells, and ADC value may have higher diagnostic efficiency.